Investigating Dual-Species Candida auris and Staphylococcal Biofilm Antiseptic Challenge - Dolunay Gülmez; Jason L. Brown; Mark C. Butcher; Christopher Delaney; Ryan Kean; Gordon Ramage; Bryn Short (MDPI AG, 2022)
Candida auris can persistently colonize human skin, alongside a diverse bacterial microbiome. In this study we aimed to investigate the efficacy of antiseptic activities on dual-species interkingdom biofilms containing staphylococci to determine if antiseptic tolerance was negatively impacted by dual-species biofilms. Chlorhexidine, povidone iodine, and hydrogen peroxide (H2O2), were able to significantly reduce biofilm viable cell counts following exposure at 2%, 10%, and 3%, respectively. Notably, H2O2-treated biofilms were able to significantly recover and considerably repopulate following treatment. Fortunately, inter-kingdom interactions in dual-species biofilms of C. auris and staphylococci did not increase the tolerance of C. auris against antiseptics in vitro. These data indicate mixed infections are manageable with chlorhexidine and povidone iodine, but caution should be exercised in the consideration of H2O2.